A Decision Support System to guide water productivity improvement: IPSR Innovation Profile - Lautze, Jonathan F.; Amarasinghe, Upali A.; Akramkhanov, Akmal (CGIAR System Organization, 2024)
Water productivity constitutes one of the key ways to expand Water Energy Food Ecosystems (WEFE) benefits in water scarce contexts. This innovation is focused on development of a Decision Support System (DSS) that enables planners and managers to identify solutions (e.g., resources allocations or crop mixes) that improve water productivity. The DSS, a computer-based platform, reveals the productivity associated with alternative investment choices, which can support investment decisions that optimize water productivity and WEFE benefits in different geographies. Key users of the DSS platform are water planners and managers, as well as those in related sectors (i.e. Energy, Food and Ecosystems).